Utilising Google Classroom as an Online Platform in Blended Learning: A Survey in UIN Raden Fatah Palembang - Amalia Hasanah (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: Google Classroom has been established since 2014. However, due to the condition happening at the moment, the use of Google Classroom has been rising. This article would like to address how students at Syariah Faculty of UIN Raden Fatah perceive Google Classroom as an online platform to support blended learning. A small survey was undertaken after the teaching and learning process ended with thirty students responded to the survey. The results of the survey showed that most students thought that Google Classroom was easy to operate and they felt convenient to use it. Therefore, they thought that Google Classroom was considered a helpful platform to support blended learning. However, because of the unfortunate circumstance due to the poor internet connection, a few students thought that Google Classroom was quite burdensome. Keywords: Google Clasroom, online, survey Abstrak: Google Classroom sudah ada sejak 2014. Tetapi, karena keadaan saat ini, penggunaan Google Classroom semakin meningkat. Tulisan ini ingin mengetahui bagaimana persepsi mahasiswa Fakultas Syariah UIN Raden Fatah tentang penggunaan Google Classroom sebagai media pembelajaran daring untuk mendukung pembelajaran campuran. Survey kecil dilakukan setelah proses belajar mengajar dengan responden sebanyak 30 orang mahasiswa. Hasil survey menunjukkan bahwa kebanyakan mahasiswa menganggap Google Classroom mudah dioperasikan dan mereka merasa nyaman menggunakannya. Oleh karena itu, mereka mengganggap Google Classroom sebagai media daring yang membantu pelaksanaan pembelajaran campuran. Tetapi, karena kondisi internet yang jelek, beberapa siswa mengatakan bahwa Google Classroom cukup merepotkan. Kata-kata kunci: Google Classroom, daring, survey